Molecular Weight Profiling Of Natural Rubber From Selected Malaysian Hevea Brasiliensis Clones And Its Relationship With Agroclimatic Parameters - Muniandy, Kavitha (2019)
Natural rubber or Hevea brasiliensis (Willd. ex A, Juss.) Mull. Arg.) inherently possesses high molecular weight (Mw) and have a wide range of molecular weight distribution (MWD) which are vital since physical properties and processing ability of rubber products are influenced by it. However, numerous aspects that may regulate rubber Mw including agroclimatical parameters are poorly investigated. Hence, this study was undertaken to profile Mw and MWD of natural rubber derived from four Malaysian clones of H. brasiliensis (RRIM 600, RRIM 929, PB350 and RRIM 3001) based on agroclimatical parameters. Latex of ten years old rubber tree were collected in a local Malaysian plantation for a duration of 12 months using gel permeation chromatography and was statistically analysed to determine factoring parameters and extent of impact on Mw trend while observing changes in Ð peak. During the experimental period, the Mw were found to be highly variable ranging from an average of 0.71 × 106 Da to 1.69 × 106 Da among the clones. PB 350 yielded rubber with consistent average Mw throughout the sampling period as compared to RRIM 600, RRIM 929 and RRIM 3001. In respect to MWD, typical unimodal and bimodal distribution were prevalent in all samples as expected. Pearson’s correlation coefficient between Mw of tested clones and agroclimatic elements showed moderate association at significance level of p=0.05. Multiple regression models were developed based on clones and agroclimatical factors to explain the variability observed in respective Mw.